YOUTH UNEMPLOYMENT: WHAT ROLE CAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PLAY IN CURBING THIS SOCIAL ILL IN SWAZILAND (ESWATINI) AND SOUTH AFRICA? (The Pretoria Student Law Review, 2021)
This profound academic opinion advocates for youth employment by clearly arguing that even though the African Youth Charter (AYC) is not binding on states in as much as on corporates/businesses, at international law these same corporates/businesses have a role to play in ensuring that youth unemployment is curbed through invoking Corporate Social Responsibility (CSR). It will be argued that CSR is no longer only associated with philanthropy, but it is now part and parcel of promoting and protecting human rights in communities where businesses operate, such that they cannot turn a blind eye to social ills such as youth unemployment.
Keywords: youth employment; African Youth Charter; Corporate Social Responsibility; human rights; corporates/businesses